Changes in wage structure in Mexico going beyond the mean: An analysis of differences in distribution, 1987 - 2008 - Claudia Tello; Raul Ramos; Manuel Artís (Institute for the Study of Labor (IZA), 2012)
This paper conducts an empirical analysis of the relationship between wage inequality, employment structure, and returns to education in urban areas of Mexico during the past two decades (1987-2008). Applying Melly's (2005) quantile regression based decomposition, we find that changes in wage inequality have been driven mainly by variations in educational wage premia. Additionally, we find that changes in employment structure, including occupation and firm size, have played a vital role. This evidence seems to suggest that the changes in wage inequality in urban Mexico cannot be interpreted in terms of a skill-biased change, but rather they are the result of an increasing demand for skills during that period.
urn:nbn:de:101:1-201301214032
Keywords: J31; 330; wage inequality; quantile regressions; decompositionwage inequality; quantile regressions; decomposition; Lohnstruktur; Arbeitsverhältnis; Bildungsertrag; Städtischer Arbeitsmarkt; Arbeitsnachfrage; Qualifikation; Schätzung; Mexiko